Bimodal magnetic resonance imaging-computed tomography nanoprobes: A Review - Fatemeh Bakhtiari-Asl; Baharak Divband; Asghar Mesbahi; Nahideh Gharehaghaji (Nanomedicine Journal, 2020)
Bimodal imaging combines two imaging modalities in order to benefit from their advantages and compensate the limitations of each modality. This technique could accurately detect diseases for diagnostic purposes. Nanoparticles simultaneously offer diagnostic data via various imaging modalities owing to their unique properties. Moreover, bimodal nanoprobes could be incorporated into theranostic systems for the design of multifunctional agents. Magnetic resonance imaging (MRI) and computed tomography (CT) are frequently used as noninvasive imaging modalities. These powerful, noninvasive diagnostic techniques used for the imaging of soft and hard tissues, respectively. However, MRI has low sensitivity and is not suitable for the imaging of bony structures. On the other hand, low soft tissue contrast is a major limitation of CT. Therefore, the development of various contrast agents that are proper for bimodal MRI/CT nanoprobes could largely influence modern medicine. This review aimed to specifically focus on the imaging properties of bimodal MRI/CT nanoprobes and their biomedical applications.